تطبيق التحول الرقمي كآلية لتحسين أداء البنوك -دراسة حالة بنك متعدد الجنسيات- - مرسي, خولة; موساوي, هاجر (جامعة الوادي - University of Eloued, 2023)
أحدث التحول الجوهري في مجال التكنولوجيا الرقمية والانتشار السريع لتقنياتها ثورة في الصناعة المصرفية، وتسعى البنوك إلى توظيف هذه التكنولوجيا وتكييفها لابتكار خدمات جديدة وتطوير أساليب تقديمها بكفاءة عالية لتصل لجميع المتعاملين على اختلافهم بدقة وسهولة وبتكلفة أقل وبالشكل الذي يدعم موقفها التنافسي ويحسنه. تسلّط هذه الورقة الضوء على مفهوم التحول الرقمي وإبراز دوره وأهميته كآلية لخلق القيمة وتحسين أداء البنوك من خلال دراسة وتحليل ثلاثة عوامل وهي: حجم العملاء والايرادات المحققة من تعاملاتهم الرقمية، تكلفة العمليات والربحية. توصلت الدراسة إلى أنّ التحول الرقمي ينطوي على مجموعة من التغييرات التّي تؤدي إلى إصلاح كل من هيكل البنك وخدماته، تعزيز العلاقة بين البنوك والعملاء وتحقيق ربح، اضافة إلى اعطاء صورة تصورية عن البنوك الرقمية الافتراضية في المستقبل. The crucial transformation in digital technology and the rapid diffusion of its applications has revolutionized the banking industry, Banks seek to employ and adapt this technology to innovate new services and develop their delivery methods with high efficiency to reach all costumers with accuracy and ease at a lower cost ; This paper sheds light on the basic concepts of the digital transformation process in banks, highlighting its role and relevance as a mechanism for improving banks' performance. For this three factors are analysed: customers and revenue from their digital transactions, cost of operations and profitability,The study found that digital transformation involves a range of changes that lead to reforming both the bank's structure and services, enhancing the relationship between banks and customers and making a profit, as well as giving a visualization of virtual digital banks in the future.
Implenting of digital transformation as a mechanism to improve banks’ performance A study of a multinational bank
مقال
Keywords: تحول رقمي ; أداء البنوك ; مؤشرات الربحية ; تقنيات رقمية: Digital transformation; Banks performance; Profitability indicators; Digital technologies.